Living with Star trek: utopia, community, self-improvement and the Star trek universe - Geraghty, Lincoln (2005)
Living with Star Trek investigates the connections between Star Trek fandom and the Star Trek text. This study identifies and examines the American themes of utopia, community and self-improvement inherent within the fictional text which also form the thematic framework for letters written by fans to express their affection for the series. These letters represent a `network of support', whereby a community of fans is able to communicate with each other through written correspondence sent to producers, edited collections, and fan magazines. In talking about the series, fans confess and share intimate stories, often based around trauma or bereavement, and at the same time describe how Star Trek has played an important and inspirational part in their daily lives; Star Trek's utopian vision and communal spirit has given them the impetus to enact positive change. Drawing together the themes identified in the text and fan letters, the first half of the thesis examines Star Trek's use of history, narrative and myth to tell its futuristic stories. In particular, I examine how Star Trek has used the distinctive literary tradition of the Puritan American Jeremiad to create a didactic narrative that emphasises the attainment of utopia through communal effort and personal change. The second half of the thesis continues this inquiry by examining a range of letters that describe how fans are able to tap into the open nature of the Star Trek text and use it to fulfil needs and desires in their own daily lives. In particular, I stress how the letters are not just examples of fan affection but also represent a reciprocal relationship where fans can criticise and engage with the programme as well as use it as a form of motivation.